ANALISIS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA LAPORAN KEBELANJUTAN BERDASARKAN GLOBAL REPORTING INITIATIVE (GRI) STANDARD - Annisa Maulia Priyo; Haryanto Haryanto (Diponegoro Journal of Accounting, 2022)
This study aims to analyze the disclosure of Corporate Social Responsibility (CSR) activities in the Sustainability Report of PT Pertamina (Persero) in 2017-2020 based on the Global Reporting Initiative (GRI) Standard. The research method used in this study is a qualitative descriptive research method with a case study approach. Data collection techniques use the method of documentation and in-depth observation of data sources as well. Data analysis is used for data processing.The type of data used in this study is secondary data obtained through the official website of PT Pertamina (Persero), namely the PT Pertamina (Persero) Sustainability Report for the 2017-2020 reporting year which has been based on the GRI Standard indicator guidelines.The results of the study show that PT Pertamina (Persero) from 2017-2020 has a focus on disclosure in the economic category and continued in the social category. Meanwhile, in the environmental category, the company is consistent with the signaling theory which states that the company always tries to disclose additional information that would add value to the company in the eyes of investors.